Drought in Ecuador - Marín-Nieto, Luis (Revista Universidad de Guayaquil, 2011)
Since 1944, when it was created the National Irrigation Board, Ecuador has not yet achieved an irrigation law for poor regions in dry areas away from natural water sources. Only in the provinces of Guayas, Manabí and Los Rios irrigation deficiencies reach a million hectares according to the MAGAP in the last Census of Agriculture. However, we could irrigate 150 000 ha of the great dry area populated only Peripa Daule Dam (3036 Hm3per year), which would be lost otherwise paradoxically part of the daily volume the ocean. A similar extension in the provinces of Bolivar and Loja and the Andean valley, have exhausted their original water sources, although there are basins in the foothills surrounding immense rivers which flow into the Atlantic Ocean. At the other end of the paradox, is the media paradigm of flood risk as the only existing hydro-type weather, while cities like Guayaquil are saturated in these provinces im[1]migrants fleeing from lack of water for their land and cattle.